2015
DOI: 10.5296/ajfa.v7i2.8550
|View full text |Cite
|
Sign up to set email alerts
|

Gender Diversity of Audit Committees and Audit Fees: Evidence from Chinese Listed Companies

Abstract: This paper investigates whether women, who serve on the audit committee of the board, can have a significant impact in reducing audit fees paid by China's A-share listed companies during the period 2004 to 2007. We show that audit committees composed of both men and ISSN 1946-052X 2015 ajfa.macrothink.org 240 women pay significantly smaller audit fees. The relationship is significantly greater in non-state enterprises than that exhibited by state-owned enterprises and significantly greater in companies deemed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 28 publications
2
16
1
4
Order By: Relevance
“…Aldamen et al, 2016;Ittonen et al, 2010;Xiang & Chengdu, 2015). Aldamen et al, 2016;Ittonen et al, 2010;Xiang & Chengdu, 2015).…”
Section: Prior Research On Gender Diversity In the Boardroom And Kaunclassified
See 3 more Smart Citations
“…Aldamen et al, 2016;Ittonen et al, 2010;Xiang & Chengdu, 2015). Aldamen et al, 2016;Ittonen et al, 2010;Xiang & Chengdu, 2015).…”
Section: Prior Research On Gender Diversity In the Boardroom And Kaunclassified
“…Regarding board composition, some studies shed light on the impact of female members on the board or audit committee and audit quality (e.g. Aldamen et al, 2016;Ittonen et al, 2010;Xiang & Chengdu, 2015). Recent empirical-quantitative research has not focused on the determinants of KAM disclosures, like the link between WOAC and auditor reporting.…”
Section: Prior Research On Gender Diversity In the Boardroom And Kamentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the previous empirical studies reviewed, it could be deduced that there are few studies [46][47][48]24,13] and [15] on the effect of audit committee gender diversity on audit fee and reported divergence results. For instance, the studies of [46,47] and [13] found that the presence of female members on the audit committee team improved the effectiveness of internal control activities, reducing the inherent risk of misstatement as well as reducing the auditor's assessment of audit risk and audit effort, thereby reducing audit fees.…”
Section: Hypotheses Developmentmentioning
confidence: 99%